2017
DOI: 10.1177/1403494817715954
|View full text |Cite
|
Sign up to set email alerts
|

How social policy contributes to the distribution of population health: the case of gender health equity

Abstract: Social policy contributes to the distribution of population health. Social-investment advocates argue such policies in particular enhance economic gender equity. Our results show that these polices have ambiguous effects on gender health equity and even differential improvements among men for some outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Our updated analysis has found an additional six reviews, but the evidence is still mixed and inconclusive. We found no studies of family policies (such as parental leave or child care) – something which is a significant evidence gap given the increasing awareness of the potential importance of such interventions for health and health equity [38, 39]. The two reviews examining income maintenance and poverty relief policies [29, 30] found financial support for poor families had no significant effects on child health but a strong relationship between unemployment generosity and improved mental health as a result of unemployment insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Our updated analysis has found an additional six reviews, but the evidence is still mixed and inconclusive. We found no studies of family policies (such as parental leave or child care) – something which is a significant evidence gap given the increasing awareness of the potential importance of such interventions for health and health equity [38, 39]. The two reviews examining income maintenance and poverty relief policies [29, 30] found financial support for poor families had no significant effects on child health but a strong relationship between unemployment generosity and improved mental health as a result of unemployment insurance.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Policies that promote greater gender equality, therefore, have the potential to modify the gender gap in LE. 22,23 Indeed, previous research shows positive correlations between gender equality and LE in both women and men, both in Europe 28 and other regions. 29 Meanwhile, some scholars highlight that if increased gender equality results only in women increasingly entering spheres traditionally occupied by men, such as the labour force and public representation, there could be diminishing gains, or losses, in health: equalising the health advantages and disadvantages of employment, but also increasing risky behaviours in women.…”
Section: Introductionmentioning
confidence: 93%
“…In this sense, the scientific literature has shown that the health of both men and women is not only different, but can also be inequitable, and the result of modifiable social factors such as social policies or distribution of resources and is therefore unfair. [22][23][24] For example, the increasing participation of women in paid work and public life has led, for many reasons, to better health outcomes for women themselves and their children, including greater access and control over economic resources. [25][26][27] Policies that promote greater gender equality, therefore, have the potential to modify the gender gap in LE.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, effects of social investment policies are only beginning to be assessed 5. One area that has not received attention is population health: social investment policies seek to enhance gender equity in European labour markets, but what effects are they having on the health of men and women?…”
Section: Introductionmentioning
confidence: 99%